The Roles of EphB2 in Cancer - Liu, Wei; Yu, Chengpeng; Li, Jianfeng; Fang, Jiwei (Frontiers in Cell and Developmental Biology, 2022)
The erythropoietin-producing hepatocellular carcinoma (Eph) receptors and their Eph receptor-interacting (ephrin) ligands together constitute a vital cell communication system with diverse roles. Experimental evidence revealed Eph receptor bidirectional signaling with both tumor-promoting and tumor-suppressing activities in different cancer types and surrounding environment. Eph receptor B2 (EphB2), an important member of the Eph receptor family, has been proved to be aberrantly expressed in many cancer types, such as colorectal cancer, gastric cancer and hepatocellular carcinoma, resulting in tumor occurrence and progression. However, there are no reviews focusing on the dual roles of EphB2 in cancer. Thus, in this paper we systematically summarize and discuss the roles of EphB2 in cancer. Firstly, we review the main biological features and the related signaling regulatory mechanisms of EphB2, and then we summarize the roles of EphB2 in cancer through current studies. Finally, we put forward our viewpoint on the future prospects of cancer research focusing on EphB2, especially with regard to the effects of EphB2 on tumor immunity.